Early diagnosis and management of 5 alpha-reductase deficiency. Issue 6 (June 1992) - Odame, I; Donaldson, M D; Wallace, A M; Cochran, W; Smith, P J
Abstract : Two siblings of Pakistani origin, karyotype 46 XY, were born with predominantly female external genitalia with minute phallus, bifid scrotum, urogenital sinus, and palpable gonads. The older sibling at the age of 8 days showed an adequate testosterone response to human chorionic gonadotrophin (hCG) stimulation. The diagnosis of 5 alpha-reductase deficiency was made at age 6 years when no 5 alpha-reduced glucocorticoid metabolites were detectable in urine even after tetracosactrin (Synacthen) stimulation. In the younger sibling the diagnosis of 5 alpha-reductase deficiency was provisionally made at the early age of 3 days on the basis of high urinary tetrahydrocortisol (THF)/allotetrahydrocortisol (5 alpha-THF) ratio and this ratio increased with age confirming the diagnosis. Plasma testosterone: dihydrotestosterone (DHT) ratio before and after hCG stimulation was within normal limits at age 3 days but was raised at age 9 months. Topical DHT cream application to the external genitalia promoted significant phallic growth in both siblings and in the older sibling corrective surgery was facilitated. In prepubertal male pseudohermaphrodites with normal or raised testosterone concentrations, phallic growth in response to DHT cream treatment could be an indirect confirmation of 5 alpha-reductase deficiency.